The Relationship between Gratitude and Body Image in X High School Students in Bandung - Lisa Widawati; Andre Kurniawan Saputra; Devi Nur Fauziah; Mutia Andini Susanti (Psikologia : Jurnal Psikologi, 2018)
Physical appearance for young women is important to show their existence. Physical and body condition and face are ideal images that are expected by every teenager. Various efforts are made by most teenagers to improve their image in order to get positive from the environment. Gratitude is important for overcoming the difficulties of excessive body maintenance. Gratitude and body image are interesting things to study so this research is to understand the relationship between gratitude and body image in Bandung X Senior High School students. The research subjects were 36 female high school students who had ideal body weight through the calculation of the Body Mess Index (BMI). The researcher developed two research measuring instruments, namely the Gratitude Scale from the concepts of Al Qayyim and Abdul Syukur and body image from Cash, 2002. The data analysis technique used was the Spearman test analysis. The results of the analysis obtained the participation coefficient r of 0.590 (p = 0,000; p> 0.05). These results indicate that there is a significant relationship between gratitude and higher body image, gratitude, the more positive the body image.